2006
DOI: 10.1039/b511563a
|View full text |Cite
|
Sign up to set email alerts
|

The chiroptical signature of achiral metal clusters induced by dissymmetric adsorbates

Abstract: Using a dissymmetrically-perturbed particle-in-a-box model, we demonstrate that the induced optical activity of chiral monolayer protected clusters, such as Whetten's Au28(SG)16 glutathione-passivated gold nanoclusters (J. Phys. Chem. B, 2000, 104, 2630-2641), could arise from symmetric metal cores perturbed by a dissymmetric or chiral field originating from the adsorbates. This finding implies that the electronic states of the nanocluster core are chiral, yet the lattice geometries of these cores need not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
169
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(179 citation statements)
references
References 18 publications
(21 reference statements)
9
169
0
1
Order By: Relevance
“…[55,69] Goldsmith and coworkers demonstrated that optical activity could arise from an achiral metal core perturbed by a dissymmetric field originating from the chiral organic shell. [56] In the intermediate model, the grand core can be achiral but the relaxation of the surface atoms involved in the adsorption of the chiral ligand creates a chiral "footprint", like that observed for adsorption of tartaric acid on Ni surfaces (C). [57] This is favored for ligands that have at least two anchoring points on the surface.…”
Section: Possible Mechanism and Theoretical Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…[55,69] Goldsmith and coworkers demonstrated that optical activity could arise from an achiral metal core perturbed by a dissymmetric field originating from the chiral organic shell. [56] In the intermediate model, the grand core can be achiral but the relaxation of the surface atoms involved in the adsorption of the chiral ligand creates a chiral "footprint", like that observed for adsorption of tartaric acid on Ni surfaces (C). [57] This is favored for ligands that have at least two anchoring points on the surface.…”
Section: Possible Mechanism and Theoretical Studiesmentioning
confidence: 98%
“…Reproduced from ref. [56] with permission of the PCCP Owner Societies. C) Chiral footprint imparted by bitartrate on NiA C H T U N G T R E N N U N G (100) surface.…”
Section: Possible Mechanism and Theoretical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[13][14][15][16][17][18][19] This shows that chirality can be bestowed to the metal. However, the question whether the metal core adopts an intrinsically chiral structure 20 or whether the chirality is only imposed on to the electronic structure of the metal core 21 remains still unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…[60] Combined with plasmonic metal materials, multifarious chiral metamolecules have been designed. [30,61,62] Com paring to the natural chiral molecule, artificial metamolecules acted as versatile platforms to manipulate electric field at the nanoscale with negative index. [63] Because SPs are sensitive to the surrounding medium, and the material permittivity and morphology, plasmonic chiral metamolecules can display strong chiroptical response and high sensitivity to the CPL incidence.…”
Section: Plasmonic Chiral Metamoleculesmentioning
confidence: 99%